TINGKAT SOSIAL EKONOMI KELUARGA ANAK PUTUS SEKOLAH DI KECAMATAN KOTO BALINGKA PASAMAN BARAT - -, Misno - (Pendidikan Geografi, 2014)
This studyaims to determine thelevel ofFamilySocioeconomicChildrenOut ofSchoolIn DistrictKotoBalingkaWest Pasamanviewsof: 1) livelihood2) education3) income4)health. This type of researchisdescriptive. The populationin this studyis thewholeentirefamilychildren out of schoolin the District ofWestPasamanKotoBalingkaconsistingoffivelocations. The sampleof respondentswastakenbytotal samplingwithsampletotaled63 people. Engineeringanalysiswithdataanalysisusingthe percentageformulaand thenusing a Likert scale. The technique ofcollectingdata throughquestionnairesor instruments. Results ofthe studyfoundthat: 1)Livelihoods familiesof school childrenin the District ofKotoBalingkaPasamanWest ingeneralasoil palm farmerswithpercentage71.43%. Andhave a second jobis alaundrywith28.57% percentage. 2) The level ofparental educationfamiliesof schoolchildrenin the District ofWest PasamankotoBalingkagenerallycomplete primary schoolwitha percentage of57.14% while the level ofeducation of their childrengenerallystopatthe highschool levelwith apercentage of39.69% its averageis26, 58with aLikert scaleof 5.32%whichisthesufficient criteria. 3) Family incomechildren out of schoolin the District ofWestPasamanKotoBalingkasourcedfrom the husbandandwifewith a percentage of36.51%, andincomecomes to aboutRp. 2,000,000withthe percentage of55.55%. 4) Familyhealthconditionof school childrenin the District ofWest PasamanKotoBalingkawellwiththepercentage of50.79%. Its averageis3.37witha 6.75Likertscalethat is onthe strongcriterion.